NLC versus nanoemulsions: Effect on physiological skin parameters during regular in vivo application and impact on drug penetration - Wolf, Martin; Klang, Victoria; Stojcic, Tatjana; Fuchs, Carola; Wolzt, Michael; Valenta, Claudia (International journal of pharmaceutics, 2018)
[Display omitted] Nanostructured lipid carriers (NLC) and nano-sized emulsions based on monoacyl-phosphatidylcholine (MAPL) were tested for their effect on physiological skin parameters in vivo during daily application over four weeks. The influence of the basic formulations on transepidermal water loss (TEWL), skin hydration, sebum content and pH was determined once per week and after a recovery period of three weeks. In addition, confocal Raman spectroscopy was employed to evaluate natural moisturising factor and urea content. The results showed that the tested NLC systems with different MAPL content led to increased TEWL and decreased stratum corneum hydration, NMF and urea content. This effect was more pronounced for NLC with higher MAPL content and less pronounced for corresponding emulsions with increased oil phase volume. The observed effects indicate temporarily impaired barrier function; however, all effects were reversible after the treatment was finished. Additional tape stripping penetration experiments were performed on intact human forearm skin in vivo using the model substance curcumin. Higher total penetrated curcumin amounts were found for NLC-based formulations when compared to the emulsion. Comparative in vitro tape stripping data on porcine ear skin confirmed the trends observed in vivo. In summary, these findings suggest that the effect of the developed MAPL-based NLC and nano-sized emulsion on skin barrier function differs mildly in a one-time application setup, but may increase strongly during daily application over a longer treatment period.